Engagement in Transformational Leadership by Teachers Influences the Levels of Self-Esteem, Motor Self-Efficacy, Enjoyment, and Intention to Be Active in Physical Education Students. - Sánchez-García, Carolina; Reigal-Garrido, Rafael Enrique; Hernández-Martos, Jacobo; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica Odilia (MDPI, 2024)
In the school context, the teacher–student interaction style plays a pivotal role in ensuring optimal adolescent functioning. Over recent years, the significance of transformational teacher leadership in fostering student engagement and positive development has been underscored. This study aimed to examine the correlations between transformational leadership and adolescent self-esteem, motor self-efficacy, enjoyment in physical education classes, and intention for future physical activity. This research used an associative and predictive strategy. A total of 429 adolescents from Málaga, aged between 14 and 16 years (M = 14.97; SD = 0.85), participated in this research, which employed an associative, comparative, and predictive approach. The Transformational Teaching Questionnaire (TTQ), Motor Self-Efficacy Scale (MSES), Intrinsic Satisfaction in Sport Instrument (SSI-EF), and Intention of Being Physically Active Scale (MIFA) were utilized for variable assessment. Correlation, Multiple Regression, and cluster analyses revealed statistically significant correlations between transformational leadership and self-esteem, motor self-efficacy, enjoyment, and future activity intention. Specifically, it was revealed that motivational inspiration predicts self-esteem, motor self-efficacy, enjoyment, and intention for physical activity, whereas intellectual stimulation predicts motor self-efficacy, enjoyment, and intention for physical activity. Notably, the transformational leadership factors of intellectual stimulation and motivational inspiration were observed to predict scores across other variables, particularly enjoyment in physical education classes, both overall and by gender. These findings suggest that transformational leadership in physical education classes can significantly enhance student experiences, thereby promoting adherence to physical activity and healthy lifestyles among adolescents.
Keywords: Educación física; Profesores de educación física; Estudiantes; Aptitudes; Hábitos; Autoconfianza; Relaciones profesor-alumno; wellness; fitness; education; positive habits; leadership; confidence; identity